Cooperative Systems Increasing the Chance of Success of Innovative Projects: A Case from the Brazilian Aerospace Sector - Michelly Karoline Alves Santana; Milton Freitas Chagas Jr. (Journal of Aerospace Technology and Management)
This paper addresses the use of cooperative systems in the management of innovative projects and their contribution to increasing the chances of success in the case study of the KC-390 Program, a significant project in the Brazilian aeronautical industry. Based on the administrative theory of cooperative systems, the study focuses on collaboration and trust in innovative projects, using the Technology Readiness Level as a guide for decisions. Complex products and systems require customized approaches due to their complexity and high engineering costs. Innovation in these projects depends on collaboration and trust between the developer and the requester. The methodology used includes applied and qualitative research, exploring bibliographic, documentary, and field research data. The KC-390 case study highlights the partnership between the Brazilian Air Force Command and Empresa Brasileira de Aeronaves (Embraer), evidencing how this relationship has been fundamental for technological development. The paper also explores the dual certification process of the KC-390, where the implementation of a collaborative process in the Conformity Demonstration Planning phase brought innovation to military certification. This innovation broke with the traditional paradigm of certification of aeronautical products in the country and was possible, mainly, due to the relationship of trust between the certifying authority and the integrating company.